Absorption, rate of accumulation and exporting of micronutrients and aluminum through tobacco (Nicotiana tabacum L.) - Cremonesi, Marcus Vinicius; Ramalho, Bruna; Golfetto, Priscila; Krepki, Luis Sergio; Pauletti, Volnei (Revista de Ciências Agroveterinárias, 2019)
Despite the historical and consolidated cultivation of tobacco in Brazil, knowledge of the demand and nutritional partition during the cycle can contribute significantly to the proper management of the crop. The objective of this study was to determine mass accumulation, absorption rates and partitioning of iron (Fe), manganese (Mn), boron (B), zinc (Zn), copper (Cu) and aluminum (Al) in tobacco (Nicotiana tabacum L.), using a widely cultivated variety in southern Brazil. This study was conducted on a tobacco property located in the municipality of Irati, PR, with a randomized block design with three replicates. The treatments consisted of ten plant collection periods at intervals of 15 days. Dry matter mass, content and daily accumulation rates of micronutrients and Al in the stem and leaves of the plant were evaluated. It was verified that the maximum accumulation of dry matter mass was close to 68 days after transplanting (DAT), and the peak of accumulation for most micronutrients occurred from 105 DAT. The order of micronutrient accumulation for tobacco was Fe>Mn>B>Zn>Cu, with maximum values obtained at 105, 135,135, 135 and 110 DAT, respectively, where more than 60% of the absorbed micronutrients were deposited on the leaves. The accumulation of Al was 36 kg ha-1, with 98.2% deposited on sheets.